Seawater intrusion assessment and prediction of sea-freshwater interface in Parangtritis coastal aquifer, South of Yogyakarta Special Province, Indonesia - Wahyu Wilopo; R Risanti; Raja Susatio; Doni Prakasa Eka Putra (Journal of Degraded and Mining Lands Management, 2021)
The Parangtritis area is a tourist destination in Yogyakarta, Indonesia, consisting of dunes and plains. One of the essential parameters in tourist areas is the provision of water sources. The increase in tourist visits and the development of tourism facilities in this area have increased groundwater utilization. Therefore, this study aims to assess the potential of seawater intrusion in the Parangtritis Beach area and its surroundings, Indonesia. The research was carried out by surveying, field measurements, and groundwater samples to test major ions in the laboratory. Indications of seawater intrusion are based on TDS values, Cl-, Simpson ratio, Sodium Chloride ratio, BEX, and groundwater type. The results showed that the research area had a shallow groundwater level with groundwater flow relative to the south-southwest and composed of unconfined aquifers. Only two water samples indicate seawater intrusion from Parangwedang spring and its southern place based on the geochemical analysis. However, this spring was formed due to geological structure related to geothermal manifestation and not due to seawater intrusion. It has a lateral flow to the south and is mixed with shallow groundwater, thereby increasing the chloride concentration in the groundwater. The sea-freshwater interface has a depth from 52 meters to 284 meters from sea level, where the farther from the coastline, the more profound.